(untitled) (Research, Society and Development, 2021)
Functional mobility can be described as the physical and motor capacity that an individual has to move around and perform daily activities that allow their autonomy; however, gradual aging causes a reduction in functional mobility, reducing the quality of life of the elderly and compromising their health. The aim of this study is to evaluate the influence of a physical exercise program on functional mobility in the elderly of an extension project of the State University of Minas Gerais Divinópolis Unit, describing its aspects in measuring the risk of falls through Time get up and go test (TUGT). This is a “before and after” longitudinal analytical study, in which data from a group of individuals were recorded using a specific and validated questionnaire for this purpose. This research, which evaluated the mobility of participants before and after a physical exercise program, used the participant as self-control. Study participants were eleven elderly women with a mean age of 66.81 years (± 6.18); all female. The main results indicate that the impairment of functional mobility aggravates the physical impacts suffered by the elderly through falls; social and environmental aspects can motivate the elderly to maintain long-term physical exercise programs. It is concluded that a consistent physical exercise routine can contribute to the maintenance or improvement of functional mobility in old age, considering the strengthening of muscle tissue and flexibility gain, which contribute to a better balance and support capacity of the body.